The Quality Of Public Services Of The Kediri City Government Through An Analysis Of Compliance With Public Service Standards - Suprastiyo, Ahmad (Fakultas Hukum Dehasen, 2025)
In the case of Kediri City, public service providers are required to comply with the established public service standards. During 2021 to 2023, the level of compliance in the provision of public services by the Kediri City Government was quite slow. The compliance index value of the Kediri City Government from 2021-2023. In 2021, the compliance value of Kediri City was 57.78 (yellow zone), in 2022 the compliance value of Kediri City was 65.22 (yellow zone) there was a fairly small increase in value of 7.44 so that it still remained in the yellow zone. Kediri City in 2023 received a compliance level value of 80.13 (green zone) there was an increase in value of 14.91 from 2022. This makes Kediri City enter the green zone, but with a lower range value in the green zone range. This study aims to analyze the level of compliance with public service standards in improving the quality of service to the community. The research method used is literature study and analysis of ombudsman report documents and the Kediri City Government through qualitative data analysis of the Spradley model. The research findings show that in the case of the Kediri City Government, the high level of compliance with public service standards is not necessarily followed by quality of service.